Effects of mycorrhizas on growth of pine seedlings (Mongolian Journal of Agricultural Sciences, 2019)
Scots pine (Pinus sylvestris) is an economically important source of timber in Mongolia and has been widely used in reforestation programs. In this study, we investigated the effects of mycorrhizas on the growth of pine (Pinus sylvestris) seedlings. Inoculation with ectomycorrhizas and endomycorrhizas increased the height, root length, and root collar diameter of the pine seedlings compared to the non-inoculated seedlings. Furthermore, the results of the study showed that the percentage survival rate is higher in mycorrhizal inoculated pine seedlings than control seedlings. These results demonstrated that inoculation could effectively form ectomycorrhizas with pine seedlings and promote its growth, which can be used to restore Mongolian forest.Нарсны тарьцын ургалтанд микоризын үзүүлэх нөлөөЭгэл нарс (Pinus sylvestris) нь Монгол орны хувьд эдийн засгийн чухал ач холбогдолтой мод бөгөөдойжуулалтанд өргөн ашигладаг. Бид энэхүү судалгаагаараа эгэл нарсны (Pinus sylvestris) тарьцныургалтанд микоризaхэрхэн нөлөөлж буйг судлав. Эктомикоризa (Pisolithus tinctorius, Lactarius laccata)болон эндомикоризийн (Glomus mosseae, Glomus spurcum хх) бэлдмэл ашиглан тарьсан тарьцын өндөр,үндэсний хүзүүвчийн диаметр болон үндэсний урт нь микоризын бэлдмэл ашиглаагүй тарьцуудтайхарьцуулахад илүү байв. Түүнчлэн микоризын бэлдмэл ашигласан тарьцуудын амьдралтын хувийнүзүүлэлт хяналтын тарьцуудаас өндөр байгааг уг судалгааны үр дүн харуулав. Дээрх үр дүнгээрмикоризын бэлдмэл нь нарсны суулгацын үндсэнд микориза болон хэлбэржиж, түүний өсөлтийгдэмжиж байгааг илрүүлсэн бөгөөд уг бэлдмэлийг ойг нөхөн сэргээхэд ашиглах боломжтой юм.Түлхүүр үг: Нарс, өндөр, үндэсний урт, диаметр